A novel predictor for the use of concurrent chemotherapy in early-stage cervical cancer with intermediate-risk factors - Chunli Fu; Cong Wang; Qiuhong Qian; Youzhong Zhang; Changdong Ma; Li Miao; Guangyu Zhang (Gynecologic Oncology Reports, 2023)
Objective: For early-stage cervical cancer patients experiencing radical surgery, postoperative radiotherapy was recommended for patients with a combination of intermediate-risk factors. However, there was no consensus on whether to administer concurrent chemotherapy. The aim of the study was to confirm the clinical value of the controlling nutritional status (CONUT) score in guiding the use of concurrent chemotherapy during postoperative radiotherapy. Methods: A total of 969 patients with FIGO stage IB-IIA cervical cancer were retrospectively analyzed. Kaplan-Meier survival analysis was performed to compare disease-free survival (DFS) and cancer-specific survival (CSS) rates between different group. A Cox proportional hazards regression test was used to conduct multivariate analyses. Results: For the patients in the high CONUT group (≥3), the addition of concurrent chemotherapy had better 5-year DFS (91.2 % vs. 72.8 %, P = 0.005) and CSS (93.8 % vs. 77.4 %, P = 0.013) than those without it. Meanwhile, the patients with concurrent chemotherapy had less rate of locoregional recurrence (8.5 % vs 16.7 %, P = 0.034) and distant metastases (11.7 % vs 30.4 %, P = 0.015). The multivariate analysis showed that concurrent chemotherapy was detected to be a factor significantly associated with DFS (P = 0.011), local control (P = 0.041), distant metastasis (P = 0.005) and CSS (P = 0.023). For the patients in low CONUT group (<3), there was no difference in prognosis between patients. Conclusion: Pretreatment CONUT score may be a predictive factor for the use of concurrent chemotherapy in early-stage cervical cancer with intermediate-risk factors during postoperative radiotherapy, and it can be helpful to determine the adjuvant treatment scheme.